(untitled) - Van der Westhuizen, Asriel

Provenance of alluvial diamonds in Southern Africa : a morphological and mineral chemistry study of diamonds and related heavy minerals from the Vaalorange system and the West Coast (Stellenbosch : Stellenbosch University, 2012)
Thesis (PhD)--Stellenbosch University, 2012.